O princípio da segurança negocial no direito societário - Bushatsky, Daniel (2016)
This doctoral thesis presents the principle of negotiating security, relating it to corporate law. For such, the principles of rules are differentiated, exposing the basic principles of corporate law, emphasizing that it is due to private autonomy that the partners subject themselves to the will of the majority in corporate resolutions, just as decisions made should follow the interests of the corporation. After this, the principle of negotiating security was conceptualized, which is sustained over 4 (four) pillars: objective good faith (loyalty), confidence theory, principle of correction (inspired by the Italian law) and private autonomy. It was asserted that loyalty, reliability, correction and subjective and objective autonomy jointly studied provide the base value for the interpretation of the Law and Legal Affairs, bringing security to corporate relations, within the legal framework of trade, creating the standard of behavior expected from all those involved in trade. By combining the principle of negotiating security with the principle of corporate preservation, it can be demonstrated how conflicts of interest involving the company, partners and administrators should be resolved. Following, first an overview of business risk and the multiple facets of justice, then a review on the legal protection of private investment, arriving at the conclusion that it must comply with its corporate function, in order to expose the main aspects of the business corporation. In order to prove the understanding, doctrinal passages were presented, recent decisions of the Brazilian courts on corporate law were analyzed, as well as how theoretical examples were used as illustration. Finally, the paper emphasizes that the principle of negotiating security must be applied in corporate law, protecting society, partners, administrators, and, thus, helping both the economic and the social development